Processed whole soybeans in growing-finishing rations - B A Koch; D T Lafferty; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1970)
This progress report covers only growth rate and feed efficiency of pigs the first 73 days of one feeding trial. Replacing soybean meal with either dry-roasted whole soybeans or pressure-extruded, whole soybeans did not significantly affect rate of growth or feed efficiency. Results were similar when the replacement was on a pound-for-pound basis or a protein-unit basis. Also, results were similar with rations in pellet or meal form. Pelleted rations were 2 to 14% more efficient than meal rations. Barrows gained 8% faster than gilts.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Soybeans; Growing-finishing rations; Barrows; Gilts